L'endométriose pariétale cicatricielle après césarienne: une entité rare - El Fahssi, Mohammed (Pan Afr Med J, 2016)
Wall endometriosis is a rare clinical entity whose pathophysiology remains unclear. It occurs most frequently after gynecologic or obstetric surgery. We report the case of a patient with cyclic pain at the caesarean section scar. Clinical examination showed a 5 cm mass in the right iliac fossa. Tomodensitometry revealed a tissue density mass (45mm on the major axis). Hence, the decision to perform a wide excision of the lesion. Anatomo-pathological examination confirmed the diagnosis of parietal endometriosis. Postoperative sequelae were simple with a follow-up period of 20 months with no recurrence of the mass or of the pain. Our study highlights the characteristics of this disease to allow the health practitioner to understand the importance of diagnosis, of early treatment of this disease as well as of the possibility to prevent it during each gynecologic or obstetric surgery.